Desempenho agronômico, valor nutricional e modelagem de respostas produtivas e fisiológicas de cultivares de milheto no semiárido - Rafael Dantas dos Santos (2016)
Faced with the second Green Revolution scenario, associated with the advent of climate change, becomes imperative to identify water-use efficient plants. In this context, pearl millet (Pennisetum glaucum (L) R) can play an important role in rainfed agricultural systems. Thus,the objective was to evaluate the agronomic performance and nutritional parameters of pearl millet cultivars for silage production; calibrate and validate a dynamic crop simulation model, aimed at its application in management strategies; and evaluate the influence of physiologicalmaturity in agronomic traits, quality and nutritional parameters of pearl millet silage. For this, were conducted four trials, distributed in three experimental stations. In Experiment 1, five pearl millet cultivars were evaluated for silage production. The biomass yield ranged from 9.9to 14.1 t/DM/ha, and digestible dry matter yield ranged from 5.0 to 7.2 t/DM/ha. In Experiment 2, under similar conditions of the previous experiment, was observed a dry matter yield ranging from 7.6 to 11.5 t/DM/ha, while the digestible dry matter yield ranged from 3.7 to 5,6 t/DM/ha. In cluster analysis was observed the formation of three distinct groups, with the group formed by CMS-03 and CMS-01 cultivars out-performed the others. In Experiment 3 were also evaluated five cultivars of millet, however beyond agronomic parameters wereobserved quality silage, intake, and digestibility. Digestible dry matter yield had an average value of 6.6 t/DM/ha. The cultivar IPA BULK1-BF had the highest percentage of panicle and in vitro digestibility of dry matter, while the BRS 1501 showed the highest concentrations of butyric acid and pH values. Intake and apparent digestibility were not influenced by cultivars. In assessing the prediction model, the experimental data from the three trials mentioned above were used. Based on long-term historical weather data, were simulated different sowing dates and evaluated the impact of this management strategy in the performance of four pearl millet cultivars. The results showed that the model was able to simulate the phenology and crop performance accurately, compared to measured data. Furthermore, it was observed that the optimum sowing window varied among locations depending on rainfall patterns, althoughshowing the same trend for cultivars within a site. For the Experiment 4 was used only one pearl millet cultivar harvested at different maturity stages. The results showed that the dry matter and digestible dry matter yield, the concentration of dry matter, carbohydrates and lignin increased with maturity increasing. However, the concentration of crude protein, intake and apparent digestibility decreased. Therefore, it concludes that the pearl millet cultivars had feasibility for forage production under semi-arid conditions. For the cultivar IPA BULK1-BF was observed potential to yield forage within a wide harvest window, which ranges between 50 and 80 days after sowing. The CSM-CERES-Pearl Millet model could be a useful tool for the definition of management strategies for the pearl millet crop at Brazilian semi-arid.